CHARACTERIZATION AND PROFILING OF SEED STORAGE PROTEINS OF SOME UNDERUTILIZED BEANS VARIETIES USING SDS-PAGE - K. O. Soetan; D. A. Animasaun (Journal of Animal and Plant Sciences, 2019)
Seed storage proteins of seventeen underutilized beans germplasm from the International Institute of Tropical Agriculture (I.I.T.A), Ibadan, Nigeria were profiled for protein composition and abundance using Sodium Dodecyl Sulphate-Polyacrylamide Gel Electrophoresis (SDS-PAGE). Electrophoregrams were analyzed by matching spot positions compared with standard protein marker (Page Ruler 10-200 kDa) in three independent replicates. Protein fractions between 11-140 kDa were detected of which high molecular mass and low mobility protein fractions were dominant. A total of 10 fractions were separated from the samples with the highest (8) found in Lima bean cultivars (2006-015, 2006-011, 2006-001) and Sword bean Tcg-1, while the least (4) occurred in Winged bean TPt-3. There were remarkable similarities between all the samples in their low-molecular mass fractions (11.0-33.3 kDa). Legumin and vicilin fractions abound in the samples, but protease inhibitor (11 kDa) present only in small quantity. The dendrogram of the similarity showed two main clusters which divided into sub-clusters of heterogeneous beans. The dendrogram revealed that Pigeon pea (CITA-2, A078-99), Jack bean TCe-5 and African yam bean TSs-10 were similar based on protein composition. Sword bean (TCg-1, TCg-4) and winged bean (TPt-06 and TPt-30) had the highest genetic distance (0.7 scale). The study concludes that SDS-PAGE is efficient for profiling and identifying pea proteins. The seed storage protein composition of the underutilized beans had basic protein fractions for their utilization as cheap sources of plant protein. Moreover, low content of protease inhibitor (11 kDa) signified low toxic constituent of pea protein which make the seed proteins of good quality for nutritional application.
Keywords: Pea seed proteins; protein profile; SDS-PAGE; underutilized beans; protease inhibitor